2018
DOI: 10.1186/s13287-018-0776-6
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal stem cell-based therapy for radiation-induced lung injury

Abstract: Since radiotherapy is widely used in managing thoracic tumors, physicians have begun to realize that radiation-induced lung injury (RILI) seriously limits the effects of radiotherapy. Unfortunately, there are still no effective methods for controlling RILI. Over the last few decades numerous studies have reported the beneficial effects of mesenchymal stem cells (MSCs) on tissue repair and regeneration. MSCs can not only differentiate into lung alveolar epithelial cells and secrete anti-inflammatory factors, bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(45 citation statements)
references
References 49 publications
(51 reference statements)
0
44
0
1
Order By: Relevance
“…Due to their capacity to suppress detrimental immune response and ability to differentiate into type II alveolar epithelial (ATII) cells in vitro , mesenchymal stem cells (MSCs) represent new players in cell-based therapy of acute and chronic inflammatory lung disorders [5, 6]. Since these adult multipotent stem cells can be readily isolated from numerous tissues (bone marrow (BM), adipose tissue (AT), amniotic fluid (AF), placenta (PL), umbilical cord (UC), peripheral blood, lungs, and deciduous teeth) and expanded with high efficiency, MSC-based therapy of lung diseases has rapidly progressed over the past decade [5].…”
Section: Introductionmentioning
confidence: 99%
“…Due to their capacity to suppress detrimental immune response and ability to differentiate into type II alveolar epithelial (ATII) cells in vitro , mesenchymal stem cells (MSCs) represent new players in cell-based therapy of acute and chronic inflammatory lung disorders [5, 6]. Since these adult multipotent stem cells can be readily isolated from numerous tissues (bone marrow (BM), adipose tissue (AT), amniotic fluid (AF), placenta (PL), umbilical cord (UC), peripheral blood, lungs, and deciduous teeth) and expanded with high efficiency, MSC-based therapy of lung diseases has rapidly progressed over the past decade [5].…”
Section: Introductionmentioning
confidence: 99%
“…and MSCs, which have been used in clinical trials as therapeutics and are becoming increasingly important for alleviating irradiated tissue damage. To date, no significant improvement has been found in clinical trials of MSC-based therapy with anti-inflammatory agents and antibiotics for RILI [ 46 ]. Although nintedanib treatment attenuates tissue fibrosis after RILI [ 16 ], our results show that nintedanib used on irradiated alveolar epithelium was not beneficial for the attenuation of regenerative lung cells.…”
Section: Discussionmentioning
confidence: 99%
“…In 2006, the international association of cell therapy (International Society for Cellular Therapy, ISCT) unified the definition of MSCs as follows: (1) adherent growth; (2) cell surface expression of certain specific antigens (markers); and (3) fat cell, osteoblast, and chondrocyte differentiation ability [ 62 ]. Since then, increasing evidence has shown that MSCs play an important role in tissue repair, regeneration, and immune regulation [ 63 66 ]. Now, the definition of MSCs has been extended, and the concept of “MSCs” as nonhematopoietic stem cells in the bone marrow was borrowed from the hypothesis of BMSCs but extended to nonskeletal tissue.…”
Section: Current Strategies For Articular Cartilage Regenerationmentioning
confidence: 99%